Influence of nickel nanoparticle-substitution on dielectric properties of P(BN)ZT ceramics - Nittaya Jaitanong (2018)
In the present study, the effect of nickel nanoparticle doping on the dielectric properties of lead bismuth niobate zirconate titanate, P(BN)ZT solid solution were investigated. P(BN)ZT powder doped with nickel in the composition of (1-x) PBNZT-xNi when x = 0.00, 0.02, 0.04, 0.06, 0.08 and 0.1 percent by mole. P(BN)ZT doped with nickel powder were calcined at 900 °C for 2 h and sintered at the temperature range of 1150 -1250°C for 2 h with heating/cooling rate of 5 °C/min. The dielectric constant (εr ) of all ceramics was measured at room temperature using LCR meter. The domain structure was observed by piezoresponse force microscopy (PFM). From the results, it can be seen that properties of P(BN)ZT ceramics with doped nickel nanoparticle change significantly with increasing nickel additive content in the system. ©2010 IEEE.